Knowledge and practice of first aid among parents attending primary health care centers in Madinah City, Saudi Arabia, A cross sectional study - Ala'a A. S Al-Johani; Samia Sabor; Samia A. R Aldubai (Journal of Family Medicine and Primary Care, 2018)
Background: Rapid and right intervention of parents can limit disability and increase the chances of survival of the injured child and make a big difference in the outcome. Objectives: The objective of this study is to assess the knowledge and practice of first aid among parents attending PHCs in Al-Madinah city, 2017. Methods: A cross-sectional study was conducted in governmental primary healthcare centers in Al-Madinah Al-Munawwarah city (Saudi Arabia) during the year 2017. A representative sample of Saudi parents who live in Madinah and came to family medicine clinic in PHC was included. A pre-validated and self-administered questionnaire was used for data collection. Results: The study included 390 parents. More than half of them (55.6%) were males. The age of 40% of them ranged between 31 and 40 years whereas that of 31.5% ranged between 20 and 30 years. Majority of the parents (97.2%) were aware of first aid. The most commonly reported source of information about first aid was mass media (59%). Majority of the parents (93.3%) believe there must be training in first aid, and only 34.6% of them claimed that they attended a training course in first aid. The highest average knowledge percentage was observed regarding the first aid of diabetes mellitus (68.8%), followed by epilepsy (49.7%), incidents (37.5%) and finally injuries/fractures (36.7%). Higher educated parents, those with a moderate number of children (4–6), those reported nurses as the main source of information, those previously attended training in first aid, and those who had experience with incidents among their children expressed higher significantly first aid knowledge compared to their counterparts. Conclusions: First aid of various illnesses among parents in Al-Madinah city is not satisfactory, particularly regarding incidents, injuries, and fractures. However, the majority of them were willing to attend training courses in first aid at primary healthcare centers.